Determinant Factors of Village-Owned Enterprise Best Practice in Indonesia - Muhammad Setiawan Kusmulyono; Wawan Dhewanto; Melia Famiola Hariadi (AGRARIS: Journal of Agribusiness and Rural Development Research, 2023)
The enactment of the Village Law marks the beginning of the rural development transformation through Village Owned Enterprise (VOE) implementation. In Indonesia, 45,549 VOEs have been established in 83,931 villages. VOEs are developed with a social business model to provide economic and social benefits to the community. Unfortunately, VOEs demonstrating satisfying performance in Indonesia have not reached 600. This research focused on discovering significant factors influencing VOEs’ ability to accomplish their best economic and social performance and proposed a success pattern that other VOEs could adapt to their natural and human assets. This study adopted a qualitative mono-method with 24 sources, varying from village government officers, directors and personnel of VOEs, academicians, and other parties, focusing on exploring three VOEs with accomplishments. The findings uncovered six propositions that must be fulfilled for VOEs to attain the necessary success concerning social and economic performance. These results suggested that the village government’s commitment, the VOEs’ management professionalism, and the village community’s involvement must cooperate to produce a balanced social and economic performance. This discovery also suggested VOEs to reflect and reproduce local knowledge trough take an advantage of their distinctive natural and human resources.